Towards a Justification the Principle of Coordination - Maarten C.W. Janssen (Tinbergen Institute, 2000)
Different variations of a Principle of Coordination are used in anumber ofdifferent research traditions. Roughly speaking, one version of thePrinciple says thatif there is a unique Pareto-efficient outcome in a game, then playerswill choose theirpart of that outcome. In this paper I will investigate thefoundations of the Principleand see to what extent the Principle follows from some axiomsregarding rationalindividual decision-making.
Keywords: 330; Spieltheorie; Theorie